Readmission from orthopedic surgical site infections: an integrative review - Torres, Lilian Machado; Turrini, Ruth Natália Teresa; Merighi, Miriam Aparecida Barbosa; Cruz, Arménio Guardado (Revista da Escola de Enfermagem da USP, 2015)
OBJECTIVE Characterizing readmissions from orthopedic surgical site infections. METHOD An integrative review of literature in the LILACS, IBECS, MEDLINE, Cochrane, SciELO and PUBMED databases, using the descriptors Patient readmission, Wound infection, Cross infection, Orthopedic procedures, Orthopedics. RESULTS 78 studies were identified and 10 publications were selected. Surgical site infections are the most common cause of unplanned orthopedic readmissions, representing long periods of hospitalization, new surgical procedures and high costs, and greater possibility of subsequent hospitalizations. Most significant predictors have indicated average length of hospitalization, need for intensive care, emergency status at admission, risk of death, age >; 65 years, males and higher body mass index. CONCLUSION Readmission rates have increasingly become measures of quality and concerns about costs. New studies could involve issues related to indirect costs, specifically social and psychological costs.